Article Commentary: Covid-19 and Persons with Substance Use Disorders: Inequities and Mitigation Strategies. Issue 3 (July 2020) - Melamed, Osnat C.; Hauck, Tanya S.; Buckley, Leslie; Selby, Peter; Mulsant, Benoit H.
The COVID-19 pandemic disproportionately disrupts the daily lives of marginalized populations. Persons with substance use disorders are a particularly vulnerable population because of their unique social and health care needs. They face significant harm from both the pandemic itself and its social and economic consequences, including marginalization in health care and social systems. Hence, we discuss: (1) why persons with substance use disorders are at increased risk for infection with COVID-19 and a severe illness course; (2) anticipated adverse consequences of COVID-19 in persons with substance use disorders; (3) challenges to health care delivery and substance use treatment programs during and after the COVID-19 pandemic; and (4) the potential impact on clinical research in substance use disorders. We offer recommendations for clinical, public health, and social policies to mitigate these challenges and to prevent negative outcomes.